Redox catalysis for energy and the environment - Llobet, Antoni, 1960-; Diéguez, Montserrat; Sala, Xavier (Advances in catalysis, 2025)
Redox Catalysis for Energy and The Environment, Volume 77 in the Advances in Catalysis series highlights new advances in the field, with this volume presenting engaging chapters written by an international board of authors. Topics covered include the development of earth-abundant molecular catalysts with redox-active ligands for artificial photosynthesis, the use of porous organic materials for photocatalytic degradation of water pollutants, supramolecular systems for chemical energy conversion, and dyadic systems for water-splitting catalysis. The volume also explores innovations in artificial photosynthesis extending beyond water splitting, aimed at applications in organic synthesis.- Provides the authority and expertise of leading contributors from an international board of authors- Presents the latest release in Advances in Catalysis serials- Updated release includes the latest information in the field.